2023
DOI: 10.3389/fpubh.2023.1129198
|View full text |Cite
|
Sign up to set email alerts
|

The stake of informing patients of the risk of hypofertility after chemotherapy for breast cancer

Abstract: IntroductionToo few women with invasive breast cancer are informed of the risk of hypofertility after chemotherapy. However, this risk can be prevented by offering gamete preservation by a specialized team. We believe that if more women were informed about gamete preservation, more of them would accept it.ObjectivesThe primary objective is to describe each step of the oncofertility care pathway from provision of information to gamete preservation. The secondary objective is to estimate the impact of not receiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Information and access to an oncofertility consultation were in uenced by the type of care structure, the woman's age, her parity at the time of diagnosis, and the metastatic status of the cancer(18). Furthermore, another regional study showed that if all women were informed of the risks of hypo fertility related to chemotherapy, then gamete preservation could be increased by 15.35% in women aged < 30 and 22.88% in women aged 30 to 35 (19). These data suggest that strategies are needed in France to improve access to fertility preservation.…”
Section: Introductionmentioning
confidence: 99%
“…Information and access to an oncofertility consultation were in uenced by the type of care structure, the woman's age, her parity at the time of diagnosis, and the metastatic status of the cancer(18). Furthermore, another regional study showed that if all women were informed of the risks of hypo fertility related to chemotherapy, then gamete preservation could be increased by 15.35% in women aged < 30 and 22.88% in women aged 30 to 35 (19). These data suggest that strategies are needed in France to improve access to fertility preservation.…”
Section: Introductionmentioning
confidence: 99%